2022
DOI: 10.3389/fpsyg.2022.939403
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Design Aesthetics on Consumers’ Purchase Intention Toward Cultural and Creative Products: Evidence From the Palace Museum in China

Abstract: As a symbol of Chinese culture, the Palace Museum undertakes the mission of spreading Chinese culture. In recent years, through the innovative integration of traditional culture, the Palace Museum has provided a series of cultural and creative products to meet consumers’ personalized expectations, which has attracted wide attention from both academia and practice. Cultural and creative products, as one of the means of cultural dissemination by museums, affect the revenue and sustainable development of museums.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
(59 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, aesthetic value has a positive and significant relationship with residents' attitudes and behavioral intention. This research finding is consistent with Li's [ 52 ] research on consumer's purchase intention toward cultural and creative products and Yu's [ 53 ] study on consumers' willingness to purchase Upcycled Products. We know that ICH is typically manifested through tangible product.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, aesthetic value has a positive and significant relationship with residents' attitudes and behavioral intention. This research finding is consistent with Li's [ 52 ] research on consumer's purchase intention toward cultural and creative products and Yu's [ 53 ] study on consumers' willingness to purchase Upcycled Products. We know that ICH is typically manifested through tangible product.…”
Section: Discussionsupporting
confidence: 90%
“…The design of cultural and creative products of sports events should reflect local culture, natural culture, humanistic culture, and other related issues. The cultural and creative product design of sports events is not a single unit, but a regional resident culture [ 8 ]. Good cultural and creative product design of sports events can not only enhance the economic status of the region but also arouse the fitness enthusiasm of local residents and promote the improvement of fitness levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lu states in previous research that usercentered products, which are based on in-depth and continuous communication between products and target customers to understand user preferences and characteristics, can promote the improvement of consumer purchase intention [12]. Yan and Wang demonstrated that corporate image, product innovation, and service quality can promote the improvement of customer value, which in turn affects purchase intention [13]. According to Liu and Hu, the higher the perceived globalization of the international brand with which the product is associated, the better the product's sales prospects [13].…”
Section: Important Resultsmentioning
confidence: 99%